Kesadaran Beragama Santri di Pondok Pesantren Abinnur Al-Islami - Anisah, Juli; Putra, Dodi Pasila (YASIN, 2023)
This research is motivated by the existence of problems that occur at the Abinnur Al-Islami Islamic Boarding School, especially class VIII, namely the religious awareness of students who are considered to be good enough as seen from awareness in carrying out religious orders such as praying on time, fasting sunnah, participating in religious activities and so on. . However, there are still students who are negligent in carrying out religious orders such as leaving prayers, delaying prayers, leaving the obligatory fast, namely during the month of Ramadan, there are still students who are lazy in participating in religious activities, tend to get emotional quickly and speak harshly, do not care about other people and so on. This study aims to determine the religious awareness of Class VIII students at the Abinnur Al-Islami Islamic Boarding School. This type of research is quantitative research that is descriptive in nature by describing, explaining and interpreting events in accordance with the facts obtained, the results of which are in the form of numbers. The population in this study was 447. The samples taken were 82 people from the population using simple random sampling technique. Data was collected using a questionnaire instrument with a Likert scale type. Data analysis techniques and raw data processing using Microsoft Excel with the percentage formula. The results of this study indicate that the religious awareness of students at the Abinnur Al-Islami Islamic Boarding School, especially Class VIII, as a whole there are two indicators that are in the medium category, namely worship awareness with 75 students in the medium category with a percentage of 91.46% and 7 students in the category low with 8.54% and indicators of awareness of the morals of students with 65 students in the medium category with a percentage of 79.27% and 17 students in the high category with a percentage of 20.73%. As for muamalah awareness with 48 people in the very low category with a percentage of 58.54% and 34 people in the low category with a percentage of 41.46% and in social awareness there are 79 students in the very low category with a percentage of 96.34% and 3 people in low category with a percentage of 3.66%. This means that the muamalah and social awareness of the santri is not good and the pesantren should understand the problems experienced by the santri, especially those related to muamalah and social awareness so that the santri can increase their muamalah and social awareness.